Aviary Wonders Inc. Spring Catalog and Instruction Manual : renewing the world's bird supply since 2031 - Samworth, Kate (Clarion Books, Houghton Mifflin Harcourt, 2014)
In a future when deforestation and other environmental factors have caused many bird species to go extinct, businessman Alfred Wallis offers a catalog of parts for creating replacements, from hand-carved beaks to Italian-leather feet.